Effect of Culture Different Profile on Growth Performance of Red Tail Mystus (Mystuswyckioides) - SINGPA, Bounlam; KANDEE, Thanousinh (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
Red Tail Mystus (Mystus wykioides) is a natural fish which founds in the Mekong River and main rivers both Thailand and Lao PDR. Now a day, the red tail mystus has decreased in numbers. This was designed to compare between 3 profiles on growth performance of Red Tail Mystus (Mystuswyckioides). with 90 days of age, 5.5±0.5 g/fish of weight and 8.01±0.1 cm/fish of length were allocate to 3 profiles raising system with earth pond (EP), concret tank (CT) and net cage (NC) at the density of 30 fishes per square meter (m2) and fed for 120 days.The results were showed that growth performance as average final body length, final body weight, average daily gain (ADG) and feed convert ratio (FCR) were higher (P<0.05) in EP than NC and CT. For survival rate was hihest (P<0.05) in EP and lowest in CT and NC. The meal characteristic of crude protein and fat were showed higher (p<0.05) in EP than NC and CT respectively. In conclusion, the profile of EP was showed higher (P<0.05) potential of growth performance, FCR, survival rate and meat quality than profile of NC and CT respectively.